2014
DOI: 10.1016/j.pedneo.2013.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Mid-upper-arm Circumference and Arm-to-height Ratio in Evaluation of Overweight and Obesity in Han Children

Abstract: This study demonstrates that MUAC and AHtR are simple, inexpensive, and accurate measurements that may be used to identify overweight and obese Han children. Compared with MUAC, AHtR is a nonage-dependent index with higher applicability to screen for overweight and obese children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
37
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 22 publications
5
37
3
1
Order By: Relevance
“…Further studies confirmed the usefulness of MUAC for obesity detection. [15][16][17] However, cut-off values for MUAC were age and gender specific and varied across ethnic groups.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Further studies confirmed the usefulness of MUAC for obesity detection. [15][16][17] However, cut-off values for MUAC were age and gender specific and varied across ethnic groups.…”
mentioning
confidence: 99%
“…[14][15][16][17] Initially, MUAC was developed as a simple and practical proxy for under-nutrition in critical conditions and in emergency settings. 18 Because of its feasibility and accuracy, MUAC has been considered for early detection of overweight and obesity.…”
mentioning
confidence: 99%
See 3 more Smart Citations